Rintaro : Japanese food from an izakaya in California - Brackett, Sylvan Mishima; Battilana, Jessica (Hardie Grant North America, 2023)
"Nestled behind a leafy courtyard in San Francisco's Mission District, with the warm glow of lanterns illuminating well-worn wood counters, Rintaro is a beautiful escape; familiar and unexpected, bold and restrained. And its food is straightforwardly delicious: dashimaki tamago, juicy and piping hot, pork gyoza, each dumpling held together by a web of crispy batter, udon with hand-rolled noodles and a hot-spring egg, and a towering melon parfait with bright melon jellies that all but burst in your mouth. This is food that tastes both like Japan and California -- not fusion food -- but the food that you'd expect if the Bay Area were a region of Japan. Rintaro, the debut cookbook from this groundbreaking restaurant, translates the experience of a Tokyo izakaya to the home kitchen. Beautiful and idiosyncratic, Rintaro is both a master class in making homemade udon noodles, and plumbs the depths of true comfort in food, with recipes like its curry rice. With over 70 recipes showcasing inspiration and detailed instruction in equal measure, Rintaro is a book for anyone who loves Japanese food, from the curious novice to expats craving the tastes of home. It is a book that blends careful mastery with the pure delight of making the tastiest food, it encourages you to find the beauty in your own terroir and the heart in your own cooking." --